KHILAFIYAH DALAM IBADAH PADA MASYARAKAT GUNUANG OMEH KABUPATEN LIMA PULUH KOTA - Vito Dasrianto; Hamda Sulfinadia (UIN Imam Bonjol Padang, 2020)
Khilafiyah that occurred in Gunuang Omeh because people worshiped to maintain what had been practiced and left behind by previous parents or scholars. A review of the results of this study shows that in general, people worship. First, people who are thick with their stance or understanding, while still practicing what they have learned from previous scholars, teachers and parents. Second, people who cannot accept differences in worship so that they establish a place of worship to worship according to the practice they believe is carried out by the elderly who are still on their stance that their practice is the most correct or in worshiping an opinion they believe in. the truth is and the people who worship are willing to accept openly the acts of worship of others who are not the same as their practice of the younger generation. Third, khilafiyyah in Gunuang Omeh District is not a new thing, this is commonplace but the scholars try to unite and provide an explanation of khilafiyah in worshiping the community even though there are still scholars who remain strong with their daily practices or imitate what has been passed on by their predecessors. Fourth, trying not to question the problem of khilâfiyah and not showing khilâfiyah in the community even though this kind of thinking is difficult to put together in the same concept among Niniak Mamak in Gunang Omeh District. Because this Niniak Mamak has a clan or leader of their people who they have to unite and provide an explanation for worshiping which they have disputed so far, but in practice Niniak Mamak is also involved in the khilafiyah sphere even though the majority of Niniak Mamak are ulama and community leaders who heard and became a role model by the people in Gunuang Omeh. Key words: Khilafiyah in Worship and Gunuang omeh society